Arcovomer passarellii Carvalho, 1954 (Amphibia: Anura: Microhylidae): distribution extension in São Paulo state, Brazil and geographic distribution map. - Malagoli, Leo R.; Condez, Thais H.; Haddad, Celio Fernando Baptista [UNESP] (My University, 2012)
The Passarelli's Frog, Arcovomer passarellii Carvalho, 1954, was registered for the first time in the city of Santos, on the seacoast of São Paulo state, extending 160 km to southwest of the distribution previously known for this species. Here we show a distribution map for an up-to-date map for A. passarelli.